Relationship Between Physical Activity and Concentration of Study of Teenagers in Yogyakarta, Indonesia - Apriana, Wieke; Sofiyya, Izka; Julia, Madarina; Huriyati, Emy (Pakistan Journal of Nutrition, 2016)
Obesity is global epidemic phenomena in both developed and developing country as in Indonesia, especially in urban area. Genetic, overeating, low physical activity and lack of sleep are risk factors of obesity. Daily activities should increase quality of sleep. In fact, lifestyle changes in teenagers like overeating and low physical activity affect their whole health, either the physical health (causing obesity) or the sleep quality. The poor quality of sleeping in teenagers with obesity cause drowsiness during learning process in the school and hypoventilation so that occurs the decreasing concentration of study in the school. The aim of this study was to investigate the relationship between physical activity and concentration of study of teenagers in Yogyakarta. The study design was observational study with cross-sectional methods. Subject were 360 high school students grades X and XI in Yogyakarta. Modified International Physical Activity Questionnaire (IPAQ), Pittsburgh Sleep Quality Index (PSQI) and Wechsler Adult Intelligence Scale (WAIS) were utilized to collect the data. Data were analyzed univariate and bivariate and tested using chi-square test. 54.7% teenagers had moderate physical activity level over 45.3% teenagers had heavy level of physical activity. Most of teenagers had good concentration of study (71.1%) and the rest of them had poor concentration of study (28.9%). Chi square test showed, there was a relationship between physical activity and concentration of study (p = 0.005) with OR value 1.98 which explains heavy activity brings about better concentration of study. So, physical activity significantly affects concentration of study of teenagers in Yogyakarta (p